The Scholar Priest in the Church of England in the Nineteenth Century - Jasper, David (Journal of Anglican studies, 2024)
The Oxford Movement in the 1830s prompted some formidable theological scholarship which profoundly affected the lives and personalities of many Oxford-educated Church of England clergymen, not a few of whom combined deeply scholarly lives with successful parish ministries. This essay examines the lives of two such men, Canon T. F. Simmons, a parish priest in Yorkshire for some thirty years, and Bishop Mandell Creighton, much of whose scholarly writing was produced in a remote Northumberland parish before his return to Cambridge and London. By the end of the century such learned clergymen were becoming a rarity in the Church of England.